PGC1α/CEBPB/CPT1A axis promotes radiation resistance of nasopharyngeal carcinoma through activating fatty acid oxidation. Issue 6 (3rd May 2019) - Du, Qianqian; Tan, Zheqiong; Shi, Feng; Tang, Min; Xie, Longlong; Zhao, Lin; Li, Yueshuo; Hu, Jianmin; Zhou, Min; Bode, Ann; Luo, Xiangjian; Cao, Ya
Abstract : The PPAR coactivator‐1α (PGC1α) is an important transcriptional co‐activator in control of fatty acid metabolism. Mitochondrial fatty acid oxidation (FAO) is the primary pathway for the degradation of fatty acids and promotes NADPH and ATP production. Our previous study demonstrated that upregulation of carnitine palmitoyl transferase 1 A (CPT1A), the key regulator of FAO, promotes radiation resistance of nasopharyngeal carcinoma (NPC). In this study, we found that high expression of PGC1α is associated with poor overall survival in NPC patients after radiation treatment. Targeting PGC1α could sensitize NPC cells to radiotherapy. Mechanically, PGC1α binds to CCAAT/enhancer binding protein β (CEBPB), a member of the transcription factor family of CEBP, to promote CPT1A transcription, resulting in activation of FAO. Our results revealed that the PGC1α/CEBPB/CPT1A/FAO signaling axis promotes radiation resistance of NPC. These findings indicate that the expression of PGC1α could be a prognostic indicator of NPC, and targeting FAO in NPC with high expression of PGC1α might improve the therapeutic efficacy of radiotherapy. Abstract : In this study, we found that high expression of PGC1α is associated with poor overall survival in NPC patients after radiation therapy. The PGC1α/CEBPB/CPT1A/FAO signaling axis promotes radiation resistance of NPC. These findings indicate that the expression of PGC1α could be a prognostic indicator of NPC, and targeting FAO in NPC with high expression of PGC1α might improve the therapeutic efficacy of radiotherapy.